Validação de método analítico para análise de amitraz em mel utilizando GC/TSD - Silva, F.S. [UNESP]; Marchi, M.R.R. [UNESP] (Editora Unesp, 2010)
Este artigo descreve a validação de método analítico para determinação do acaricida amitraz em mel utilizando extração com n-hexano/acetona, cleanup em cartucho de extração em fase sólida (SPE) e análise por cromatografia a gás com detector termoiônico seletivo (GC-TSD). O método pode ser utilizado para monitorar a presença do pesticida amitraz em mel, devido aos bons parâmetros analíticos, precisão (CV<11%) e exatidão (>80%) dentro do intervalo 100-400 ng g-1. O limite estabelecido na União Européia, pelo Committee for Veterinary Medicinal Products, para amitraz em mel (200 ng g-1) está dentro deste intervalo. A resposta do sistema analítico apresentou linearidade entre 100 e 800 ng mL-1 com coeficiente de correlação de 0,9996, limite de detecção (LD-7 ng g-1) e de quantificação (LQ-100 ng g-1). O método validado foi utilizado para avaliar a qualidade de méis comercializados na cidade de Araraquara/SP, nas quais não foram detectados resíduos de amitraz.

This paper describes the validation of method for analysis of the acaricide amitraz in honey using n-hexane/acetone extraction, cleanup in cartridge of solid phase extraction (SPE) and analysis by gas chromatography with nitrogen-phosphorus detector (GC -TSD). The method can be used to monitor the presence of the pesticide amitraz in honey because of its good analytical parameters, precision (CV <11%) and accuracy (> 80%) in the range of 100-400 ng g-1. The limit set in the European Union, by Committee for Veterinary Medicinal Products, for amitraz in honey (200 ng g-1) is within this range. The response of the analytical system was linear between 100 and 800 ng mL-1 with correlation coefficient of 0.9996, limit of detection (LD -7 ng g-1) and quantification (LQ -100 ng g-1). The sample was fortified at three concentrations 100 ng g-1, 200 ng g-1 and 400 ng g-1, giving an average recovery of 80, 88 and 92% respectively. The validated method was used to assess the quality of honey sold in the city of Araraquara/SP, in which there were no residues of amitraz.
Validation of the analytical method for analysis of the amitraz in honey using GC-TSD
Keywords: Amitraz; validação analítica; mel; GC-TSD; Amitraz; validation method; honey; GC-TSD